Qurʾān and Sunna or the Madhhabs?: A Salafi Polemic Against Islamic Legal Tradition - Hamdeh, Emad (Islamic law and society, 2017)
The Albanian scholar Muḥammad Nāṣir al-Dīn al-Albānī (d. 1999) established a unique type of Salafism, a movement whose adherents follow a puritanical model of Muslim creed, exegesis, and conduct that is critical of madhhab Traditionalism. In this article I present an annotated translation of an audio lecture in which Albānī attempted to defend Salafism against its anti-madhhab image. I shed light on the religious and social climate that played a critical role in triggering Albānī’s disdain for Traditionalism and led him to discredit madhhab Traditionalist fiqh and replace it with his own interpretation of the jurisprudential requirements of Islamic scripture. Among the arguments I make is that Albānī’s claim to follow only the Qurʾān and Sunna is a rhetorical strategy designed to present Salafism as the absolute truth and distinguish it from being categorized as another madhhab or religious movement.